Pathways to the common core : accelerating achievement - Calkins, Lucy, 1951-; Ehrenworth, Mary.; Lehman, Christopher (Portsmouth, NH : Heinemann, 2012)
Lucy Calkins and her colleagues at the Reading and Writing Project have helped thousands of educators design their own pathways to the Common Core. Now, with Pathways to the Common Core, they are ready to help you find your way. Designed for teachers, school leaders, and professional learning communities looking to navigate the gap between their current literacy practices and the ideals of the Common Core, Pathways to the Common Core will help you: understand what the standards say, suggest, and what they don't say; recognize the guiding principles that underpin the reading and writing standards; identify how the Common Core's infrastructure supports a spiraling K-12 literacy curriculum; and scrutinize the context in which the CCSS were written and are being unrolled. In addition to offering an analytical study of the standards, this guide will also help you and your colleagues implement the standards in ways that lift the level of teaching and learning throughout your school.
An introduction to the common core state standards -- Reading standards -- Overview of the reading standards : What do they say and what does this mean for us? -- Literal understanding and text complexity : Standards 1 and 10 -- Reading literature : Standards 2-9 -- Reading informational texts : Standards 2-9 -- Writing standards -- Overview of the writing standards : What do they say and what does this mean for us? -- The CCSS and composing narrative texts -- The CCSS and composing argument texts -- The CCSS and composing informational texts -- Speaking/listening and language standards -- Overview of the speaking and listening and of the language standards : What do they say and what does this mean for us? -- CCSS-Aligned assessments fuel whole-school reform.
Includes bibliographical references and index.
Keywords: Education -- Standards -- United States; Academic achievement -- United States; Reading -- United States; Language arts -- United States; Academic achievement; Education -- Standards; Language arts; Reading; United States